PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 019 SEKELADI - Suriana, Suriana; Noviana, Edddy; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem this research does because the students achievement of social studies fourth graderes students at SDN 019 Sekeladi still low with an average value 57.60 and Minimum completeness criteria ( KKM ) social studies is 65. Between students, which amounting to 23 students only 6 students completeness. Formulation of the problem "is the implementation of learning model Problem Based Instruction ( PBI ) can improve students achievement of social studies fourth grade students at SDN 019 Sekeladi districts of Tanah Putih ?”. This study aims to improve the students achievement of social studies fourth graderes students at SDN 019 Sekeladi districts of Tanah Putih with implementation learning model Problem Based Instruction ( PBI ). The research was conducted on the date of March 10, 2017 until April 05, 2017. Subjects were fourth graderes at SDN 019 Sekeladi by totaling 23 studens ,7 boys students and 16 gils students. Data collection instruments in this thesis is the a teacher activities and students and achievement students. From the results of the research activities of the teacher in the learning process in the first cycle with the first meeting of an average of 62,50 % and the second meeting improve to 75,00 %. In the second cycle the first meeting 80,00%, and the second meeting improve 87,50%. The results of the data analysis of student activity in the first cycle the first meeting of the two meeting 60.00% and the second meeting improve 70,00%. In the second cycle the first meeting of the two meeting 77,50% and the second meeting improve to 85,00%. Based on the results of the data analysis, the average students achievement before the action the point of average 57,60 (category less). After the action in the first cycle with the average of 66,08 (category enough). In the second cycle meeting improve with the average of 75,43 (category good). Mean that the implementation of learning model Problem Based Instruction ( PBI ) can improve the students achievement of social studies at fourth graderes SDN 019 Sekeladi districts Tanah Putih.Key words: Model Learning of Problem Based Instruction ( PBM ) , fourthgraderes Students Achievement